2022
DOI: 10.1103/physrevx.12.011025
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of the Electrically Triggered Insulator-Metal Transition in V3O5 Far below the Transition Temperature

Abstract: Resistive switching is one of the key phenomena for applications such as nonvolatile memories or neuromorphic computing. V3O5, a compound of the vanadium oxide Magnéli series, is one of the rare materials to exhibit an insulator-metal transition (IMT) above room temperature (Tc ~ 415 K). Here we demonstrate both static dc resistive switching (RS) and fast oscillatory spiking regimes in V3O5 devices at room temperature (120 K below the phase transition temperature) by applying an electric field. We use operando… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 54 publications
2
9
0
Order By: Relevance
“…On the other hand, electric field-induced IMT in a two-terminal device constructed by VO 2 films can produce the filamentary conducting channel from the original insulation layer. The conducting filament has been imaged on the basis of the distribution of temperature, crystal phase, or optical reflectivity (16)(17)(18)(19)(20). The quantum sensor based on a nitrogen-vacancy (NV) center in diamond enables synchronous measurement of local magnetic field and temperature on VO 2 film, providing an unusual insight into the field-induced IMT (25,37).…”
Section: Properties Of Vo 2 Film and Imaging Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, electric field-induced IMT in a two-terminal device constructed by VO 2 films can produce the filamentary conducting channel from the original insulation layer. The conducting filament has been imaged on the basis of the distribution of temperature, crystal phase, or optical reflectivity (16)(17)(18)(19)(20). The quantum sensor based on a nitrogen-vacancy (NV) center in diamond enables synchronous measurement of local magnetic field and temperature on VO 2 film, providing an unusual insight into the field-induced IMT (25,37).…”
Section: Properties Of Vo 2 Film and Imaging Approachmentioning
confidence: 99%
“…Because of the strongly correlated property, the insulator-metal transition (IMT) in Mott materials induces a huge change in resistivity, and it can be triggered by electric field, enabling applications on artificial synapses (15)(16)(17)(18)(19)(20). Selective phase transition based on the external stimuli manipulates the formation of the conducting filament although its location is still unchangeable (21).…”
Section: Introductionmentioning
confidence: 99%
“…This behavior was the basis of the neuristor proposed in 2012. 162 In more recent work, Adda et al 163,164 imaged and studied the dynamics of these oscillations in detail. Systems of oscillators can show complex emergent dynamical behavior, as known from the behavior of coupled pendulums, 165 ranging from synchronization to chaotic motion.…”
Section: Neural Network a Charge Currentsmentioning
confidence: 99%
“…Materials with metal-insulator phase transitions have been considered particularly promising for device applications because of the highly reliable high-operation-speed conductivity changes in the materials driven by the transitions. 1,2) By applying electric fields or injecting currents, a variety of nonlinear transport properties have been demonstrated in the materials with metal-insulator transitions, [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] and important application functions have been derived from the transport nonlinearity. In principle, materials with metal-insulator phase transitions show sharp resistive switching 4,5,8,10,12,14,17,18,[20][21][22][23] and negative differential resistance (NDR) [3][4][5][6][7][8][9][10][11][13][14][15][16]…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have revealed that the limited controllability of the nonlinear transport phenomena is mainly attributable to the induction mechanisms predominated by Joule heating. 7,11,[16][17][18][19][20] In materials that show clear temperature-induced metal-insulator transitions (such as VO 2 ), the nonlinear transport phenomena in the current-voltage characteristics have been reported to be dominantly caused by the temperature-driven transitions in most cases, which are triggered by filamentary thermal runaway in the materials via Joule self-heating. 7,16,[18][19][20] The current-voltage characteristics are thus generally discontinuous, and the nonlinear transport properties in the materials are generally hard to control because of the difficulty in controlling the abrupt thermal runaway.…”
Section: Introductionmentioning
confidence: 99%